2004
DOI: 10.1080/00423110412331291562
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Power Management for a Hydraulic Hybrid Delivery Truck

Abstract: SUMMARYHydraulic hybrid propulsion and energy storage components demonstrate characteristics that are very different from their electric counterparts, thus requiring unique control strategies. This paper presents a methodology for developing a power management strategy tailored specifically to a parallel Hydraulic Hybrid Vehicle (HHV) configured for a medium-size delivery truck.The Hydraulic H ybrid Vehicle is modelled in the MATLAB/SIMULINK environment to facilitate system integration and control studies . A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
140
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(140 citation statements)
references
References 10 publications
0
140
0
Order By: Relevance
“…Different alternatives are described, with electric hybridization , Bauman et al 2008, Khaligh et Zhihao 2010, Garcia et al 2004, Araujo et al 2014, Thoungtong et al 2009, Camara et al 2008, Li et al 2012, M. Esfahanian et al 2013, D.Chindamo et al 2013) and hydraulic hybridization (Baseley et al 2007, Filipi and Kim 2010, Kim and Filipi 2007, Wu et al 2002, Wohlgemuth 2013, Surampudi 2009) being the most typical ones.…”
Section: *Corresponding Author E-mail: Fsoriano@rosrocacommentioning
confidence: 99%
“…Different alternatives are described, with electric hybridization , Bauman et al 2008, Khaligh et Zhihao 2010, Garcia et al 2004, Araujo et al 2014, Thoungtong et al 2009, Camara et al 2008, Li et al 2012, M. Esfahanian et al 2013, D.Chindamo et al 2013) and hydraulic hybridization (Baseley et al 2007, Filipi and Kim 2010, Kim and Filipi 2007, Wu et al 2002, Wohlgemuth 2013, Surampudi 2009) being the most typical ones.…”
Section: *Corresponding Author E-mail: Fsoriano@rosrocacommentioning
confidence: 99%
“…[8] showed that by considering the reference value for the accumulator's pressure as a function of vehicle velocity demand, the modulated-pressure control strategy produces an improvement in fuel economy. A schematic for this control strategy is shown in Figure 6.…”
Section: Thermostatic Control Strategymentioning
confidence: 99%
“…The thermostatic control approach is traditionally utilized for series hybrid electric vehicles (HEVs) and adopted for HHVs [6,8]. The concept of a thermostatic control algorithm is shown in Figure 5.…”
Section: Thermostatic Control Strategymentioning
confidence: 99%
“…The powertrain system simulation has been validated with vehicle test data from proving ground [25] and subsequently thoroughly updated to represent HMMWV [26]. The hydraulic components were added to the vehicle simulation in context of parallel [27] and series hybrid systems [24]. Table 1 gives the specification of the vehicle and powertrain.…”
Section: Hybrid Vehicle Supervisory Controller Problemmentioning
confidence: 99%